2015
DOI: 10.1021/acscatal.5b00668
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Dual Role of Titanium Dioxide in the Visible Light Heterogeneous Catalyzed C–H Arylation of Heteroarenes

Abstract: The direct arylation of heteroaromatics with an easily accessible and recyclable, heterogeneous TiO 2 catalyst and visible light was developed. Electron-rich as well as electron-poor heteroarenes could be applied in this transformation, and the corresponding products were isolated in very good yields. Azoethers were detected as reactive intermediates, and the unexpected role of TiO 2 in their formation as well as reaction was established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 87 publications
2
82
1
2
Order By: Relevance
“…Such photocatalyzed reactions can be conducted with a number of aryl radical precursors including diazonium and iodonium salts, diazoanhydrides, carboxylic acids, azo sulfones, and iodo‐, bromo‐, and chloroarenes . Typically employed photocatalysts are complexes of ruthenium or iridium, eosin Y, titanium dioxide,, or strong electron donors, and double excitation of perylene bisimide recently allowed the conversion of aryl chlorides …”
Section: Methodsmentioning
confidence: 99%
“…Such photocatalyzed reactions can be conducted with a number of aryl radical precursors including diazonium and iodonium salts, diazoanhydrides, carboxylic acids, azo sulfones, and iodo‐, bromo‐, and chloroarenes . Typically employed photocatalysts are complexes of ruthenium or iridium, eosin Y, titanium dioxide,, or strong electron donors, and double excitation of perylene bisimide recently allowed the conversion of aryl chlorides …”
Section: Methodsmentioning
confidence: 99%
“…[6e] TheU V/Vis absorption spectrum of (4-CF 3 C 6 H 4 ) 3 PAuCl showed av ery weak absorption band at 450 nm (e = 17), which excludes the possibility of (4-CF 3 C 6 H 4 ) 3 PAuCl being aphotosensitizer itself.Alight on/off experiment showed that the transformation required continuous irradiation with blue LEDs (see the Supporting Information), excluding the possibility that an efficient radical-chain propagation mechanism is operating. [11] However,d espite the fact that these species might also be formed in the gold-catalyzed process,their role in the reaction remains unclear. We assume that the reaction is initiated by goldinduced single electron transfer (SET) to the aryl diazonium salt, generating an aryl diazo radical and gold(II) species A.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Rueping et al used TiO 2 to mediate the intermolecular coupling between arenediazonium salts and heteroaromatics (Scheme ) . They found that the reaction proceeds through formation of TiO 2 ‐azoethers, which undergoes excitation upon the visible light irradiation.…”
Section: C–c Bond: Sp2‐sp2 Disconnectionmentioning
confidence: 99%